Towards Equity: Projecting and Converging the Human Development Index in Indonesia - Nayaka Artha Wicesa,; Axellina Muara Setyanti; Silvi Asna Prestianawati (Jurnal Ekonomi Kuantitatif Terapan, 2024)
Human development has become an imperative for Indonesia amid the ongoingdemographic bonus. However, various challenges persist in the realm of humandevelopment in the country, as evidenced by disparities in Human Development Index(HDI) achievements. This research aims to project Indonesia's HDI for the years 2023, 2024,2035, and the "Golden Indonesia" period in 2045 to discern the developmental trajectory ofHDI and its disparities. Additionally, it seeks to measure the convergence of Indonesia's HDIto attain equitable development. The results of the trend projection estimations indicate thatIndonesia's HDI is projected to be 73.74 in 2023 and 74.28 in 2024, which is anticipated to fallbelow the target set by the government, aiming for an HDI of 75.54 in 2024. Indonesia's HDIis projected to reach 80.22 in 2035 and 85.62 in 2045, categorizing it as 'Very High,' aligningwith the vision for the Golden Indonesia in 2045. Furthermore, conditional convergenceanalysis results indicate that it would take 75 years for provinces with lower HDI to catch upwith those with higher HDI, achieving zero inequality. Based on the estimation results, it isfound that Per Capita Spending on Educational Functions is a significant variableinfluencing HDI convergence.